Simple technique for generating trains of ultrashort pulses. - Robinson, T; O'Keeffe, K; Landreman, M; Hooker, S; Zepf, M; Dromey, B (2007)
A simple method for generating trains of high-contrast femtosecond pulses is proposed and demonstrated: a linearly polarized, frequency-chirped laser pulse is passed through a multiple-order wave plate and a linear polarizer. It is shown theoretically that this arrangement forms a train of laser pulses, and in experiments the production of a train of approximately 100 pulses, each of 200 fs duration, is demonstrated. In combination with an acousto-optic programmable dispersive filter this technique could be used to generate and control pulse trains with chirped spacing. Pulse trains of this type have widespread applications in ultrafast optics.